2021
DOI: 10.5296/jpag.v11i1.18006
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability Features, Proactivity, and Change Readiness: An Empirical Investigation of Public Sector Organisations

Abstract: This study examined the mediating role of proactivity in the effects of five adaptability features (i.e. work stress coping, creativity, dealing with uncertainty, training and learning, and interpersonal adaptability) on employees’ change readiness. A total of 379 employees of public sector organisations in Malaysia participated in the study. Partial Least Squares-Structural Equation Modelling (PLS-SEM) was employed to analyse the proposed model. The results indicate that out of the five adaptability features,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…The findings emphasized that individuals with a proactive approach and planfulness ability have a positive outlook toward the technological changes and adaptations in the organization, resulting in overall organizational success. These findings are in line with the recent research findings, which suggested that intentional behavior (Tan & Nadarajah, 2021) and planfulness (Dobrovič & Timková, 2017) are necessary antecedents in enhancing the employees' readiness for change.…”
Section: Practical Implicationssupporting
confidence: 92%
See 1 more Smart Citation
“…The findings emphasized that individuals with a proactive approach and planfulness ability have a positive outlook toward the technological changes and adaptations in the organization, resulting in overall organizational success. These findings are in line with the recent research findings, which suggested that intentional behavior (Tan & Nadarajah, 2021) and planfulness (Dobrovič & Timková, 2017) are necessary antecedents in enhancing the employees' readiness for change.…”
Section: Practical Implicationssupporting
confidence: 92%
“…Existing studies indicated that intentional behavior has been associated with various positive outcomes, including risk-taking capability, enhanced individual performance, and organizational effectiveness (Tornau & Frese, 2013). Tan & Nadarajah (2021) collected a sample of 379 public sector employees and highlighted the positive role of intentional and proactive behavior in enhancing the employee's readiness for change. These findings are also confirmed by the research performed by Bakker et al (2012).…”
Section: Intentional Behaviour and Readiness For Changementioning
confidence: 99%